Evaluating the Efficacy of Eradicating Gardnerella vaginalis Vaginal Colonization With Amoxicillin: A Randomized, Double-Blind, Phase 2 Study. Issue 2 (February 2022) - McNeil, Candice J.; Tan, Amy; Powell, Jonathan A.; Pontius, Angela; Lewis, Andrea; Myler, Noelle; Schwebke, Jane R.
Abstract : Background: Research suggests that Gardnerella vaginalis (GV) is the keystone pathogen in bacterial vaginosis (BV). Knowledge gaps exist regarding the role of GV eradication in the development of BV. This study was designed to test the hypothesis that vaginal colonization with GV could be eradicated by treatment of women without BV with amoxicillin, a drug highly active against GV. If GV is necessary for the development of BV, then eradication of GV may prevent the development of BV. Methods: We conducted a randomized control trial of amoxicillin 500 mg twice daily versus placebo for 7 days in women aged 18 to 45 years without vaginitis who screened positive for vaginal colonization with GV by quantitative polymerase chain reaction. Test-of-cure visit for GV was conducted at day 21. Results: One hundred seventy-two women met preliminary criteria and were screened for enrollment. Ninety-seven GV-positive women were randomized to receive amoxicillin versus placebo. Eradication of GV occurred in 21% of women randomized to amoxicillin versus 16% on placebo ( P = 0.757). In the 4 weeks between screening and test-of-cure visit, 16 of 92 (17%) of participants developed Nugent scores greater than 3 with 8 of 92 (9%) having BV. All of these were in participants in whom GV was not eradicated ( P = 0.035). Conclusions: The study failed to show a benefit of treatment with amoxicillin to eradicate GV. No participants in whom GV was eradicated had progression to abnormal vaginal flora during the study period. Abstract : Treatment with amoxicillin versus placebo showed no significant difference in eradicating Gardnerella vaginalis . Progression to abnormal vaginal flora did not occur in any woman with eradication of G. vaginalis .